Cannot Extubate a Newborn Patient after an Arterial Switch Operation? Check Major Aortopulmonary Collaterals! - Tanıdır,Ibrahim Cansaran (2020)
Abstract The standard treatment of transposition of the great arteries is the arterial switch operation (ASO). Despite successful surgical correction, patients cannot tolerate extubation after the operation. Major aortopulmonary collaterals (MAPCAs) are one of the rare causes of prolonged mechanical ventilation due to significant hemodynamic effects. We report a 28-day-old newborn with transposition of the great arteries and a ventricular septal defect (VSD) who underwent ASO and VSD closure. After postoperative extubation failed twice, four large MAPCAs were revealed during heart catheterization. After transcatheter closure of these four MAPCAs, the patient was extubated and discharged 27 days after the procedure.